Ileal long-segment ischemia after the unintended ligation of variant ileal branch during laparoscopic right hemicolectomy - Gyung Mo Son; Tae Un Kim; Dong-Hoon Shin; Joo-Young Na; In Young Lee; Shin Hoo Park (Journal of Minimally Invasive Surgery)
The variant terminal trunk of the superior mesenteric artery (SMA) could be confused with the ileocolic artery (ICA) as it runs on the right side of the superior mesenteric vein. If the variant ileal branch of SMA is mistaken for the ICA, unintentional ligation could cause long-segment ischemia in the ileum. We encountered a rare case of ileal ischemia caused by unintentional ligation of the variant ileal branch of the SMA during laparoscopic right hemicolectomy, which was confirmed by indocyanine green (ICG) angiography and hyperspectral imaging (HSI). Intraoperative real-time perfusion monitoring using ICG angiography and tissue oxygen saturation monitoring using HSI could help detect segments of hypoperfusion and prevent hypoperfusion-related anastomotic complications.